EC to launch joint cyber unit. Issue 7 (July 2021) - Unknown
Abstract : The European Commission (EC) has announced plans to build a Joint Cyber Unit to combat cybercrime across the EU. And it is looking to all players in this area – private companies as well as government bodies and law enforcement – to share data and resources.